Anticariogenic potential of white cheese, xylitol chewing gum, and black tea - Gul, Pinar (Eur J Dent, 2018)
OBJECTIVE: This study aimed to examine the effects of these foods on plaque pH and the potential development of tooth decay. MATERIALS AND METHODS: Plaque pH was measured using the sampling method before and after 1, 5, 10, 20, 30, 45, and 60 min following consumption of these foods individually and after rinsing with a 10% sucrose solution. Statistical analysis was performed using one-way ANOVA and Tukey honestly significant difference post hoc tests (α = 0.05). RESULTS: Although there were statistically significant differences in all test groups except the BT (P = 0.620) and sucrose + XCG (P = 0.550) groups in time, none of the participants chosen for this study were having a plaque pH value anywhere close to the critical value (pH = 5.5). CONCLUSION: WC, BT, and XCG are advisable as anticariogenic foods because pH values are not below critical value.